Modulation of Antimicrobial Resistance in Listeria monocytogenes via Synergistic Interactions Between Thymbra capitata L. (Cav.) Essential Oil and Conventional Antibiotics - Francesca Maggio; Francesco Buccioni; Stefania Garzoli; Antonello Paparella; Annalisa Serio (Antibiotics, 2025)
Background/Objectives: Antimicrobial resistance (AMR) poses a significant global health challenge, contributing to foodborne infections and diminishing the effectiveness of conventional antibiotics. In the quest for alternative strategies to mitigate resistance, this study has assessed the potential of T. capitata L. (Cav.) essential oil (TEO) to boost the antibiotic efficacy on L. monocytogenes. Methods: Five L. monocytogenes strains of different origins were tested with TEO alone and in combination with gentamicin, ampicillin, and penicillin G. Moreover, the cells were exposed to sublethal concentrations of TEO for 1 h to evaluate the effects on the antibiotic effectiveness. The antimicrobial activity was assessed by determining the Minimum Inhibitory (MICs) and Bactericidal Concentrations (MBCs), while potential interactions were evaluated using the Fractional Inhibitory Concentration Index and by studying the cell growth dynamics. Results: TEO demonstrated inhibitory activity against L. monocytogenes strains, both alone, in pre-exposure, and in combination with antibiotics, causing up to a seven-fold reduction in MIC and MBC values (from 8 to 1 µg/mL) and restoring susceptibility to the antimicrobial treatments. Positive interactions between TEO and antibiotics were observed, particularly for clinical isolates. Conclusions: TEO could be a promising antibiotic adjuvant in antimicrobial treatments, offering a natural and effective strategy to enhance antibiotic efficacy and to counteract resistance in L. monocytogenes.